Fabrication and Efficient Acidichromism of Langmuir-Blodgett Films of Azo Group-Modified Phthalocyanines - Li, Jianqiang (Asian Journal of Chemistry, 2012)
Langmuir-Blodgett thin films of the azo group-modified phthalocyanines are successfully prepared. The aggregated and acidichromic properties of Langmuir-Blodgett films has been investigated.